Polyploidy in Cupressaceae: Discovery of a new naturally occurring tetraploid, Xanthocyparis vietnamensis. Issue 4 (28th July 2021) - Farhat, Perla; Siljak‐Yakovlev, Sonja; Hidalgo, Oriane; Rushforth, Keith; Bartel, Jim A.; Valentin, Nicolas; Leitch, Ilia J.; Adams, Robert P.
Abstract: While polyploidy (whole‐genome multiplication) is generally considered rare in extant gymnosperms (with the exception of Ephedra, Ephedraceae), the occurrence of sporadic polyploid individuals belonging to various genera in the conifer family Cupressaceae has been reported in the literature. In addition, recent studies have revealed that polyploidy is not uncommon in the genus Juniperus (Cupressaceae), with tetraploid and hexaploid individuals reported in individuals collected from wild populations. Given these findings, we undertook a comprehensive screening of ploidy levels in 32 species belonging to the four genera that are phylogenetically closest to Juniperus (i.e., Callitropsis, Hesperocyparis, Xanthocyparis, and Cupressus ), referred to as the CaHXCu complex. In addition, we also determined the ploidy level of two accessions in the poorly studied tetraploid, Fitzroya cupressoides . Using flow cytometry together with published chromosome counts to assign ploidy levels, we show that all species of the CaHXCu complex are diploid except Xanthocyparis vietnamensis, which is tetraploid, with a genome size of 44.60 pg/2 C. This study opens up new opportunities for studying the impact and consequences of polyploidy on the evolution and adaptation of species in Cupressaceae. Abstract :